Kajian Karakteristik Proses Pengomposan Limbah Tanaman Jagung yang Diberi Tambahan Kipahit dan Pupuk Kandang Sapi - Sophia Dwiratna; Edy Suryadi; Dwi Rustam Kendarto; Kharistya Amaru; Wahyu Kristian Sugandi; Nur Ilham Tri Hartono (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
Corn waste, tithonia and cattle manure are three materials that have different characteristics. These charactersitics differences if used together in the composting process will  complement each other and potentially produce good compost. This research was conducted to find out how the composting process characteristics by utilizing the three raw materials with different characteristics in a composting process. The composting process was carried out using a berkeley method which was stacked with a layered bioreactor. The decomposition process that occurs involving decompisted bacteria, so the composting process runs aerobically. Aerobic composting  corn waste with the addition of tithonia and cattle manure finished in about 4-5 weeks to become a mature compost. The quality of the compost produced is quite good because the content contained in compost fulfills most of the quality standards regulated in SNI 7763: 2018. The addition of tithonia and cattle manure has a positive impact in the process of composting corn plants in terms of duration and good compost. Key words : aerobic, cattle manure, composting, corn waste, tithonia